(untitled) (Journal of Society of Surgeons of Nepal, 2022)
Introduction: The COVID-19 pandemic has had a major impact on healthcare in many countries. This study assessed the effect of a nationwide lockdown during the second wave of COVID-19 on surgical management for acute surgical conditions and the subsequent impact on postoperative mortality. Methods: This was a retrospective study, evaluating data from the hospital discharge database during the second wave of COVID -19 pandemic. All adult patients admitted through the emergency and outpatient department requiring surgical treatment between April 29 and June 29, 2021 were included in the study. The primary outcome was the change in number of hospital admissions for acute surgical conditions. Mortality was assessed among the patients with COVID-19 infected cases. Results: During the second wave of nationwide COVID-19 lockdown period, a total of 329 patients were provided surgical consultation either in emergency or outpatient basis. Among them, 227 cases required surgery. Out of this 122(53.74%) required minor surgeries and were performed in minor operation theatre in local anesthesia (LA) while 105(46.2%) underwent major surgical procedures. Of all the patients who underwent major surgical procedures 76(72.3%) were surgical emergencies, 15(14.2%) were GI and breast malignancies while 14(13.3 %) were elective cases. The mortality rate due to COVID-19 in surgical patients was 02(16.66 %) during the lockdown period. Conclusion: A decrease in hospital admissions for elective surgical cases with prioritization to emergency and malignant cases was observed during the lockdown period.